2014
DOI: 10.1097/brs.0000000000000063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fatigue Strength of C2 Pedicle Screws, C2 Pars Screws, and a Hybrid Construct in C1–C2 Fixation

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 26 publications
(17 reference statements)
1
35
0
Order By: Relevance
“…The direction of the screw is 15 -30 medial and 20 -25 cephalad. Although a biomechanical study has shown that C2 pedicle screws have twice the pullout strength of C2 pars screws [68], the clinical results of the two fixation techniques are similar [69]. Both the C2 pedicle screw and C2 pars screw are widely used for screw-rod system fixation of C1-C2 fusion [69].…”
Section: C2 Pedicle Screw Techniquementioning
confidence: 98%
“…The direction of the screw is 15 -30 medial and 20 -25 cephalad. Although a biomechanical study has shown that C2 pedicle screws have twice the pullout strength of C2 pars screws [68], the clinical results of the two fixation techniques are similar [69]. Both the C2 pedicle screw and C2 pars screw are widely used for screw-rod system fixation of C1-C2 fusion [69].…”
Section: C2 Pedicle Screw Techniquementioning
confidence: 98%
“…The pullout strength of a C-2 pedicle screw is greater than that of the pars. 34 In very young children, the pars may be quite small and only allow a few threads of screw purchase; therefore, a pedicle screw may be preferred if anatomically feasible. This may require threading the screw through a very narrow area.…”
Section: Discussionmentioning
confidence: 99%
“…The C-2 pars lies between the inferior and superior articular facet, whereas the pedicle connects the inferior articular facet to the vertebral body. 8,34 Both the pars and pedicle are potential targets for instrumentation. The pullout strength of a C-2 pedicle screw is greater than that of the pars.…”
Section: Discussionmentioning
confidence: 99%
“…pedicle screws, bilateral pars screws and hybrid of unilateral pars screw with contralateral pedicle screw combinations all showed the ability to limit range of motion and significantly decreased after cyclical testing in flexion-extension, lateral bending, and axial rotation. They concluded that in situations with anatomical limitations like a high-riding or medialized vertebral artery, the unilateral C2 pedicle screw along with a contralateral short pars screw is a viable biomechanical option that may be as stable as a bilateral pedicle screw construct (26).…”
Section: █ Conclusionmentioning
confidence: 99%
“…Ebraheim et al described the C2 pedicle as a dense bone that connects the inferior articular fascet to the C2 vertebral body, and C2 pars as a trabecular bone between superior and inferior articular processes. The distinction between these two different structures is much more significant for confrontation with situations such as a high-riding or medialized vertebral artery, in which a long C2 pedicle screw places the vertebral artery at risk (5,26).…”
Section: █ Conclusionmentioning
confidence: 99%